COMPARATIVE RESEARCH OF EMPATHY AMONG RUSSIAN AND CHINESE STUDENTS - J. V. Lebedeva (Russian State Vocational Pedagogical University, 2016)
The aim of this work is the study of the universal and specific characteristics of empathy of students from Russia and China.Methods. The methods involve the analysis and generalization of literature on the concept and structure of empathy, the influence of cultural factors on this phenomenon. The research is performed in line with the cross-cultural approach. Data are obtained using two methods: «Diagnostics of the level of poly-communications empathy» by I. M. Yusupov and «Diagnostics of the level of empathic abilities» by V. V. Boyko (in the modification of V. V. Boyko and O. A. Klitsenko).Results. The influence of cultural factor the formation of the components of empathy and the severity of the empathy towards various social objects are analyzed. Specific characteristics of empathy of students from Russia (generalization, association, high severity emotional component of empathy) and from China (differentiation and selective empathy) are detected. Two universal characteristics are founded: empathy to the parents to be stronger than for other social objects, and also equally expressed the cognitive component of empathy.Scientific novelty. The study has proved that it is not enough to examine only the level of development of empathy. It is necessary to study its emotional and cognitive components, as well as orientation towards various social objects.Practical significance. Recommendations for creation of more comfortable and safe educational environment in Russian Higher educational institutions for students from China are proposed.